Pengaruh Teknik Sterilisasi dan Komposisi Medium terhadap Pertumbuhan Tunas Eksplan Sirsak Ratu - Sulistiyo, Rico Hutama; Luthfiyyah, Zayyan; Susilo, Buana; Dalimartha, Lengga Nurullah; Wiguna, Eko Chandra; Yuliana, Nuniek; Prasetyo, Nugroho (Universitas Sebelas Maret, 2017)
Successful tissue culture of soursop plants requires proper sterilization techniques and hormone levels toproduce good shoot growth. This study aims to determine the effect of sterilization techniques and mediumcomposition of soursop explants, using factorial completely randomized design with 2 factors: sterilizing agentsand medium composition, repeated 3 times. Hydrogen Peroxide, Mercury and Sodium Hypoclorite used assterilizing agents. The medium composition used in this study consisted of 3 levels: MS 0, MS 0.5 ppm BAP+ 0.05 ppm NAA and MS 1 ppm BAP + 0.1 ppm NAA. The best treatment is MS medium 0.5 ppm BAP + 0.05ppm NAA with hydrogen peroxide sterilizing agent which produces the highest propagation level and lowestcontamination level.